2018
DOI: 10.4103/2045-9912.229596
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen inhalation improves mouse neurological outcomes after cerebral ischemia/reperfusion independent of anti-necroptosis

Abstract: This study aimed to investigate the role of necroptosis in the neuroprotection of hydrogen in a mouse model of cerebral ischemia/reperfusion (I/R) injury. C57BL mice were randomly divided into sham group, I/R group, hydrogen/oxygen group (HO), nitrogen/oxygen group (NO). Middle cerebral artery occlusion (MCAO) for 1 hour followed by reperfusion was introduced to animals which were allowed to inhale 66.7% hydrogen/33.3% oxygen for 90 minutes since the beginning of reperfusion. Mice in NO group inhaled 66.7% nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…In addition, the oxygen concentration was at a higher than normal level in the hydrogen mixture produced by the electrolysis of water. Although our previous study showed 66.7% nitrogen and 33.3% oxygen had no significant influence, the effects of elevated oxygen concentration should be confirmed by investigation (Huang et al, 2018).…”
Section: Discussionmentioning
confidence: 61%
“…In addition, the oxygen concentration was at a higher than normal level in the hydrogen mixture produced by the electrolysis of water. Although our previous study showed 66.7% nitrogen and 33.3% oxygen had no significant influence, the effects of elevated oxygen concentration should be confirmed by investigation (Huang et al, 2018).…”
Section: Discussionmentioning
confidence: 61%
“…Hydroxyl radicals are the most cytotoxic of ROS; H 2 has a strong ability to eliminate hydroxyl radicals and peroxynitrite [ 22 , 24 ]. Previous researches have demonstrated 67% H 2 and 33% O 2 mixture gas strikingly decreased ROS induced by ischemia-reperfusion in the brain [ 34 , 50 ], liver [ 51 ], and heart [ 52 ] in animal models. Clinical studies have reported 67% H 2 and 33% O 2 mixture reduced the inspiratory effort in patients with acute severe tracheal stenosis [ 53 ] and restored the exhausted supply of CD8+ T cells in patients with advanced colorectal cancer [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although cell death due to primary HI insult was not preventable, the delayed cell death of both necrosis and apoptosis appeared to be reduced in this study. In one study of a HI mouse model, inhalation of high-concentration H 2 improved the neurological outcome and reduced infarct size and oedema after cerebral ischaemia/reperfusion, even though H 2 acts independently of antinecroptosis pathways 19 .…”
Section: Discussionmentioning
confidence: 99%